Pengaruh Keselamatan Kesehatan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan PT Gapura Angkasa Terminal 3 Bandara Soekarno Hatta Pada Masa Pandemi Tahun 2021 - Rustandi, Lola Violetta; Sihombing, Sarinah; Suhaedi, Eddy (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2022)
The purpose of this study was to determine and analyze the simultaneous effect of occupational health safety and work discipline on employee performance of PT Gapura Angkasa Terminal 3 Soekarno-Hatta Airport during the 2021 pandemic with quantitative approach method and the data collection method was in the form of field research, and library research data. The data analysis method used are Multiple Linear Regression Analysis, Multiple Correlation, Coefficient of Determination (R2 Test), F Statistics Test, and T Test and the results of this study indicate that the F test result shows that the score of F value = 354,564 > F table = 3,12 that means occupational health and safety and work discipline simultaneously have a significant effect on employee performance on PT Gapura Angkasa Terminal 3 Soekarno-Hatta Airport during the 2021 pandemic.